EFEKTIVITAS IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK (SRA) DAN KONTRIBUSINYA TERHADAP PEMBANGUNAN EKONOMI BERKELANJUTAN DI KABUPATEN BERAU - NANCY APRILIANTY AJANG (ECO-BUILD, 2026)
This study evaluates the effectiveness of the Child-Friendly School (Sekolah Ramah Anak/SRA) program in Berau Regency, East Kalimantan, and analyzes its contribution to sustainable economic development. Using a mixed-methods approach, data were collected from 27 respondents (principals, teachers, students, and parents) at the kindergarten/early childhood education, elementary, and junior high school levels through questionnaires and in-depth interviews. The quantitative results show that SRA implementation in Berau Regency is fairly effective, with the highest success rate at the junior high school level (84.07%), followed by kindergarten/early childhood education (81.11%) and elementary school (80.00%). Most SRA indicators, such as a safe, clean, and inclusive learning environment, have been well implemented.However, the study also identifies notable challenges, including limited School Health Unit (UKS) facilities, a lack of special programs for children with special needs, and variation in teachers' understanding of positive discipline. Qualitatively, SRA has proven instrumental in shaping students' character, instilling positive values such as cleanliness, tolerance, and cooperation, and developing 21st-century skills including critical thinking, collaboration, and innovation. This contribution directly supports the improvement of human resource quality and the strengthening of the local economy through community collaboration. These findings confirm that SRA implementation aligns with the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education), Goal 5 (Gender Equality), and Goal 8 (Decent Work and Economic Growth), positioning it as a long-term strategic investment for sustainable regional development.